Participatory agro-ecosystem analysis and identification of problems in Garhkundar-Dabar Watershed of Central India - Palsaniya, D.R.; Singh, Ramesh; Yadav, R.S.; Tewari, R.K.; Dwivedi, R.P.; Kumar, R.V.; Venkatesh, A.; Kareemulla, K.; Bajpai, C.K.; Singh, Rajendra; Yadav, S.P.S.; Chaturvedi, O.P.; et al. (Indian Journal of Agroforestry, 2020)
The studies on participatory agro-ecosystem analysis and identification of problems conducted in Dabar- Garhkundar watershed of Tikamgarh, M.P. are presented in this paper. This watershed has an area of 850 ha and supports nearly 191 farm families having 2648 animal resources. Rainfed agro ecosystem covers the major area and hardly 20% of the cultivated area is under irrigation and that too supplemental only. The cropping systems are dominated by cereals as seen from crop diversification which shows that in a particular year the cultivated area is highest under cereals (46%) followed by pulses (22%), oilseeds (20%) and others (12%). The productivity of the crops is low. The soil types of the watershed are locally known as Rakar and Parwa which are the variants ofthe red soils and are poor in fertility due to coarse texture, shallow depth, low water retention capacity, low organic matter and multiple slopes. The watershed area is rich in floral and animal wealth and the number of animals per household worked out to be 13.9 while the number of animals per person was 2.9. They play an important role in livelihood security of the people through drought proofing. However, the milk productivity in terms of litres/day/animal is low and varies between 3-5 for buffaloes, 1-2 for cows and 0.250-0.500 in case of goats. While analyzing the system properties and problems, "low productivity of crops and animals due to water scarcity" was emerged as the topmost problem and based on this, our team proposed a "model watershed project on natural resource management through agroforestry interventions" to address the problems and bring livelihood security and sustainability in agricultural production in the area.